2017
DOI: 10.1186/s12885-017-3473-4
|View full text |Cite
|
Sign up to set email alerts
|

JMJD2A promotes the Warburg effect and nasopharyngeal carcinoma progression by transactivating LDHA expression

Abstract: BackgroundJumonji C domain 2A (JMJD2A), as a histone demethylases, plays a vital role in tumorigenesis and progression. But, its functions and underlying mechanisms of JMJD2A in nasopharyngeal carcinoma (NPC) metabolism are remained to be clarified. In this study, we investigated glycolysis regulation by JMJD2A in NPC and the possible mechanism.MethodsJMJD2A expression was detected by Western blotting and Reverse transcription quantitative real-time PCR analysis. Then, we knocked down and ectopically expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 38 publications
2
28
1
Order By: Relevance
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…Thus, in many types of spontaneous cancers (e.g., pancreatic cancer, prostate cancer, gliomas and cutaneous melanoma metastases), an elevated LDHA expression is observed compared to normal tissues [22,23,24,25]. High levels of LDHA were confirmed also in gastric cancer (HER2 positive tumors have a significantly higher LDHA level than HER2 negative), and nasopharyngeal carcinoma [26,27]. Elevated levels of LDHA in tumor cells are considered as their metabolic adaptation to anaerobic glycolysis [23,24,25,26].…”
Section: Lactate Dehydrogenases and Lactatementioning
confidence: 99%
“…In the glycolytic pathway, lactate dehydrogenase A (LDHA) irreversibly catalyzes the conversion of pyruvate to lactate via the oxidative dehydrogenation of nicotinamide adenine dinucleotide (NADH) to NAD+. Several studies have reported that LDHA is highly expressed in various cancers such as pancreatic cancer, gastric, gallbladder, and breast cancers, as well as nasopharyngeal and hepatocellular carcinomas; its expression is positively correlated with the malignant progression of the cancers (9)(10)(11)(12)(13)(14)(15). However, the relationship between LDHA expression and the progression of OSCC, as well as the underlying mechanisms that affect the biological behavior of OSCC cells, are still unclear.…”
Section: Introductionmentioning
confidence: 99%